Neighbourhood, school and home food environment associations with dietary behaviours in Hong Kong adolescents: the iHealth study - Soloveva, Maria V.; Barnett, Anthony; Mellecker, Robin; Sit, Cindy; Lai, Poh-chin; Zhang, Casper J.P.; Sallis, James F.; Cerin, Ester (Health & place, 2025)
This study is the first to examine whether neighbourhood, school and home food environments were associated with dietary behaviours in Hong Kong adolescents; and whether off-campus lunch school policy, bringing lunch from home and parental rules for eating behaviours moderated the associations. We used data from the international Healthy environments and active living in teenagers – (Hong Kong) [iHealt(H)] study. Participants were healthy adolescents aged 11–18 years (N = 1299; Mage = 14.7 years; 57 % girls) and their parent/primary caregivers. Participants completed surveys with validated scales to assess dietary behaviours and perceived food environments. The Microscale Audit of Pedestrian Streetscapes and Geographic Information Systems data and software were used to objectively assess food environments. A higher number of bakeries, coffee shops, cafes and convenience stores in the neighbourhood was associated with higher consumption of vegetables and lower consumption of sugar-sweetened drinks in adolescents. Adolescents who frequently brought lunch from home to school consumed fatty foods and sugar-sweetened drinks less frequently and were more likely to eat fruits and vegetables. Greater availability of unhealthy food outlets at the school was associated with higher consumption of sugar-sweetened drinks, whereas more restaurants around the school was associated with higher consumption of fruits and vegetables. Home-made lunches and restrictive parental eating rules moderated the effects of food environments on adolescents’ dietary behaviours. All food environmental contexts were associated with Hong Kong adolescents’ dietary behaviours; however, the home and school environment appeared to be the most influential and should be targeted in public health interventions. •Availability of healthy foods at home contributes to adolescents' healthier diets.•Healthy food outlets and restaurants should be available near schools.•Adolescents who bring home-made lunches to school are likely to eat healthier.•Parents are advised to control adolescents' consumption of unhealthy foods.